The Importance of Sociology of Education for a Sustainable Future - Serpa, Sandro; José Sá, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book offers insights on the contributions that Sociology of Education, in a broad sense (encompassing the most diverse formal, non-formal and informal processes of education, instruction, schooling and/or socialization), can provide in the analysis of sustainable development in diverse contexts and publics, respecting its paradigmatic plurality.